Internal Carotid Artery Hypoplasia: Role of Color‐Coded Carotid Duplex Sonography. (11th September 2015) - Chen, Pei-Ya; Liu, Hung-Yu; Lim, Kun-Eng; Lin, Shinn-Kuang
Abstract : Objectives: The purpose of this study was to determine the role of color‐coded carotid duplex sonography for diagnosis of internal carotid artery hypoplasia. Methods: We retrospectively reviewed 25, 000 color‐coded carotid duplex sonograms in our neurosonographic database to establish more diagnostic criteria for internal carotid artery hypoplasia. Results: A definitive diagnosis of internal carotid artery hypoplasia was made in 9 patients. Diagnostic findings on color‐coded carotid duplex imaging include a long segmental small‐caliber lumen (52% diameter) with markedly decreased flow (13% flow volume) in the affected internal carotid artery relative to the contralateral side but without intraluminal lesions. Indirect findings included markedly increased total flow volume (an increase of 133%) in both vertebral arteries, antegrade ipsilateral ophthalmic arterial flow, and a reduced vessel diameter with increased flow resistance in the ipsilateral common carotid artery. Ten patients with distal internal carotid artery dissection showed a similar color‐coded duplex pattern, but the reductions in the internal and common carotid artery diameters and increase in collateral flow from the vertebral artery were less prominent than those in hypoplasia. The ipsilateral ophthalmic arterial flow was retrograde in 40% of patients with distal internal carotid artery dissection. In addition, thin‐section axial and sagittal computed tomograms of the skull base could show the small diameter of the carotid canal in internal carotid artery hypoplasia and help distinguish hypoplasia from distal internal carotid artery dissection. Conclusions: Color‐coded carotid duplex sonography provides important clues for establishing a diagnosis of internal carotid artery hypoplasia. A hypoplastic carotid canal can be shown by thin‐section axial and sagittal skull base computed tomography to confirm the final diagnosis.